2016
DOI: 10.1017/s1755773916000205
|View full text |Cite
|
Sign up to set email alerts
|

Constraints, competition, and competitiveness: explaining the non-linear effect of democratization on political budget cycles

Abstract: The literature on political budget cycles (PBCs) does not offer a full-fledged theory about the effect of democratization. However, it does imply a non-linear effect along the regime spectrum: positive at the autocratic end, negative at the democratic end. We theoretically develop and empirically test this implication by pointing to two countervailing effects of democratization:executive constraintsandpolitical competition. While the former contains PBCs, the latter stimulates them. Because of their empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…The same difference in amplitudes are discernible in the aftermath of elections. Therefore, we get these first visual hints towards our hypothesis that elections could have an impact on fiscal policy, as well as that the outcomewise type of elections could be a worthwhile angle to investigate, also in the light of previous research (Eibl and Lynge-Mangueira, 2017;Lami et al, 2021). Of course, although the conclusions of this paper are consistent with indications from Fig.…”
Section: Electionssupporting
confidence: 58%
See 2 more Smart Citations
“…The same difference in amplitudes are discernible in the aftermath of elections. Therefore, we get these first visual hints towards our hypothesis that elections could have an impact on fiscal policy, as well as that the outcomewise type of elections could be a worthwhile angle to investigate, also in the light of previous research (Eibl and Lynge-Mangueira, 2017;Lami et al, 2021). Of course, although the conclusions of this paper are consistent with indications from Fig.…”
Section: Electionssupporting
confidence: 58%
“…We investigate also how PBCs are affected by "electoral competitiveness", which is a germane dimension of analysis in the case of Albania, following the conceptualization of this aspect by Eibl and Lynge-Mangueira (2017) as explained in the third section below. The empirical approach we follow to test for this dimension of PBCs in Albania is the same as in Lami et al (2021) who make an outcome-wise categorization of elections (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results are found by Vergne (2009), based on a sample of 42 lower‐income countries and extending from 1975 to 2001. Eibl and Lynge‐Mangueira (2017) underline the mediating effect of electoral competitiveness on the PBC (measured by way of the budget deficit) using a sample of up to 112 countries from 1960 to 2006.…”
Section: Conditional Pbcs: Previous Work and The Role Of Time Preferencementioning
confidence: 99%
“…A growing body of work has proposed that the existence and strength of PBCs may depend on a range of conditioning or mediating variables (for reviews and empirical evidence, see de Haan & Klomp, 2013 and Klomp & de Haan, 2013). These include the level of democracy or electoral competitiveness (Block, 2002; Eibl & Lynge‐Mangueira, 2017; Gonzalez, 2002; Vergne, 2009), electoral rules and government types (Chang, 2008; Persson & Tabellini, 2003), democratic experience (Brender & Drazen, 2005); the quality of governance and the share of informed voters in the electorate (Alt & Rose, 2009; Janků & Libich, 2019; Shi & Svensson, 2006; Veiga et al, 2017; Vergne, 2009); fiscal transparency and political polarization (Alt & Lassen, 2006), checks and balances (Alt & Rose, 2009; Chang, 2008; Garmann, 2018; Streb et al, 2009; Streb & Torrens, 2013), and party age (Hanusch & Keefer, 2014). Taken together, this body of work has found that PBCs are stronger in the presence of greater electoral competition, proportional electoral rules and presidential systems, less experience with democracy, poorer quality of governance, fewer informed voters, less fiscal transparency, greater political polarization, fewer checks and balances, and younger political parties.…”
Section: Introductionmentioning
confidence: 99%